2009
DOI: 10.1016/j.jadohealth.2008.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Text4Health: A Qualitative Evaluation of Parental Readiness for Text Message Immunization Reminders

Abstract: 75%, Fisher exact p ¼ 0.83). Adjusting for weekend vs. weekday, participants who used substances on a given day were more likely to have sex (OR ¼ 1.53, p ¼ 0.04), but tended to be less likely to not use a condom (OR ¼ 0.75, p ¼ 0.08) on that day. Probability of substance use occurring 2, 6, or 12 hours before sex was 0.12, 0.21, and 0.28, respectively. Substance use was not associated with subsequent condom nonuse (OR ¼ 0.69, 0.78, 0.89, p ¼ 0.21, 0.23, 0.58 for 2, 6, and 12 hours, respectively). Conclusions:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 7 publications
4
20
0
Order By: Relevance
“…In focus groups of parents of adolescents, we found that many of them preferred them to mail or phone reminders. 58 In a study of low-income parents in Kansas, 90% of those surveyed were open to text messages from their doctor or nurse; 71 we found similar rates in a group of low-income families in New York City. 62 In a national study, 56% of the 1612 parents surveyed were willing to register their cell number with their child's usual vaccination provider, and another 18% were undecided.…”
Section: Technology-based Interventions To Improve Vaccinationmentioning
confidence: 53%
See 3 more Smart Citations
“…In focus groups of parents of adolescents, we found that many of them preferred them to mail or phone reminders. 58 In a study of low-income parents in Kansas, 90% of those surveyed were open to text messages from their doctor or nurse; 71 we found similar rates in a group of low-income families in New York City. 62 In a national study, 56% of the 1612 parents surveyed were willing to register their cell number with their child's usual vaccination provider, and another 18% were undecided.…”
Section: Technology-based Interventions To Improve Vaccinationmentioning
confidence: 53%
“…62 In a national study, 56% of the 1612 parents surveyed were willing to register their cell number with their child's usual vaccination provider, and another 18% were undecided. 60 Parents prefer text messages that are simple, short and personalized and include provider information 58,62,72 Although to date text message interventions have focused on parents, as older adolescents play a role in vaccine decision-making, they can also be recipients of vaccine reminders. 73 Provider interest in text messaging has been mixed.…”
Section: Technology-based Interventions To Improve Vaccinationmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas previous studies have evaluated influenza vaccinations with survey data 5 or retrospectively with claims data, 2,6 no study has prospectively quantified influenza vaccination in US pediatricians' offices. Strategies proposed to increase vaccine uptake include standing orders, reminder/recall systems, after-hours and weekend vaccination clinics, offering influenza vaccination to parents, and parent/patient letters, posters, flyers, phone calls, text messages 7 and Emails. 2,[8][9][10] Increased knowledge of the various tactics actually used by pediatric offices to deliver the influenza vaccine to children may help inform national recommendations by organizations such as the US Centers for Disease Control and Prevention (CDC) and the American Academy of Pediatrics.…”
Section: Introductionmentioning
confidence: 99%